Carry this book - Jacobson, Abbi (Viking, an imprint of Penguin Random House LLC, 2016)
How many self-tanning lotions are in Donald Trump's weekender? What's inside Martha Stewart's hand-knit fanny pack? What kind of protein bars does Michelle Obama hide in her tiny clutch at the White House Correspondents Dinner? Carry This Book provides a humorous and insightful look into how the things we carry around every day can make up who we are.